Ethics of Learners in the Quranic Perspective - Yuliana Siregar (Journal of Education and Teaching Learning, 2022)
In the Islamic tradition, studying is an obligation. In order to obtain knowledge, there are several ethics that need to be considered by students. This is what currently feels like it is starting to disappear, many students no longer pay attention to ethical issues in studying. Ethics is very important to pay attention to so that the knowledge gained is useful. This study aims to uncover the ethics of students in the perspective of the Qur’an. This research uses the literature study method by tracing the opinions of interpretation (mufassir) and other authoritative sources or documents. The results of this study show that the most important thing in studying is to maintain ethics so that the knowledge sought can enter the heart and be useful in its practice. Among the ethics of students in studying according to the concept of the Qur'an are 1) the intention of learning for worship and drawing closer to Allah swt., 2) being humble (tawadhu'), 3), learning gradually, and 4) learning completely.